East meets West Japanese income tourism: A proposal to improve luxury hotels management strategy - Tavares de Carvalho, P.; Reis, E. (Proceedings of The 49th Conference of the European International Business Academy, 2023)
The main goal of this study is to understand the strategy of Portuguese luxury hotels (before and after covid-19), concerning Japanese tourists, identifying the customers factors of satisfaction or dissatisfaction with hotel attributes, explaining the gap between expectations versus perceptions. The study was based on qualitative and quantitative research methods, taking a three-step approach: first, the relevant literature was reviewed for a better understanding of Japanese culture, Japanese tourists, and the keys to success of hotel management; second, content analysis was conducted of “booking.com” online customers review for Lisbon (1.354 hotel guests: 538 Japanese and 816 Chinese) to compare satisfaction and dissatisfaction with hotel attributes. Some exploratory interviews revealed that in Portugal, Asian tourists are considered, in general, as Chinese, so Chinese tourists were introduced in the study, third: 501 questionnaires had been sent to managers. The study has theoretical and practical implications to the hospitality sector, a plan to improve hotels strategy is presented in a fourdimensional approach (Market, Processes/Procedures, People and Finance/Price), Customer as an umbrella dimension. A new dimension had been discovered: “Features”. The study was made in Portugal, but the plan of improvement proposed, can be applied to other western countries.